2021
DOI: 10.1108/rausp-11-2020-0253
|View full text |Cite
|
Sign up to set email alerts
|

Countries’ governance and competitiveness: business environment mediating effect

Abstract: Purpose The purpose of this study is to analyze how institutional governance and business environment affect countries’ competitiveness and their relative importance. Design/methodology/approach In this paper, the authors analyze how institutional governance and business environment affect countries’ competitiveness, their relative importance and what are the implications for Brazil. The authors have collected data from 131 countries related to the institutional governance, business environment and competiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…The scientists are unified in the belief that the quality of the institutions is a foundation for competitiveness (see : Bontempo, 2022;Ervits, Zmuda, 2018;Guerrieri, Meliciani, 2004;Hollingsworth, 2000;Ingram, Silverman, 2000;Jaffe et al, 1993;Moon et al, 1998;Peng et al, 2008;Porter, 1990;Porter, Linde, 1995;Rodriguez et al, 2005;Soete, 1987;Tobey, 1990;Wan, Hoskisson, 2003). stated that "property rights institutions have a first-order effect on long-run economic growth, investment, and financial development".…”
Section: Theoretical and Methodological Foundations Of The Research P...mentioning
confidence: 99%
“…The scientists are unified in the belief that the quality of the institutions is a foundation for competitiveness (see : Bontempo, 2022;Ervits, Zmuda, 2018;Guerrieri, Meliciani, 2004;Hollingsworth, 2000;Ingram, Silverman, 2000;Jaffe et al, 1993;Moon et al, 1998;Peng et al, 2008;Porter, 1990;Porter, Linde, 1995;Rodriguez et al, 2005;Soete, 1987;Tobey, 1990;Wan, Hoskisson, 2003). stated that "property rights institutions have a first-order effect on long-run economic growth, investment, and financial development".…”
Section: Theoretical and Methodological Foundations Of The Research P...mentioning
confidence: 99%
“…A favorable business environment can effectively promote the digital transformation of enterprises. Optimizing the business environment means liberating productivity and enhancing competitiveness [48]. Firstly, from the perspective of enterprises, the digital transformation of enterprises is a long-term systematic reform project in production, sales, management, and other aspects, characterized by high costs, high risks, and long cycles [49].…”
Section: Digital Government and Enterprise Digital Transformation: Th...mentioning
confidence: 99%
“…They also found that corruption had a very substantial delayed influence on reported SWB but no immediate impact. Bontempo (2022) [4] examined the relative weights of institutional governance and the business environment as they relate to competitiveness and what those factors mean for Brazil. Data on institutional governance, the business environment, and the competitiveness of 131 nations have been gathered by the authors.…”
Section: Research Reviewmentioning
confidence: 99%
“…For example, China is a contemporary single-party-led economy that does not hold any direct elections at the national level whereas India is a parliamentary democratic secular republic in which the president of India is the head of state & first citizen of India and the prime minister of India is the head of government (Geddes, Wright, and Frantz, 2018; Öniş & Gençer, 2018) [11,18] . Hence, they differ in ease of doing business, competitiveness, and international standing (Bontempo, 2022) [4] .…”
Section: Introductionmentioning
confidence: 99%